2017
DOI: 10.1371/journal.pntd.0005436
|View full text |Cite
|
Sign up to set email alerts
|

Different genotypes of Trypanosoma cruzi produce distinctive placental environment genetic response in chronic experimental infection

Abstract: Congenital infection of Trypanosoma cruzi allows transmission of this parasite through generations. Despite the problematic that this entails, little is known about the placenta environment genetic response produced against infection. We performed functional genomics by microarray analysis in C57Bl/6J mice comparing placentas from uninfected animals and from animals infected with two different T. cruzi strains: K98, a clone of the non-lethal myotropic CA-I strain (TcI), and VD (TcVI), isolated from a human cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…In addition, ECM components, that are synthetized by the resident cells are also present in tissue and organ samples [ 18 , 19 ]. Similar results have been obtained in animal models, where important changes in murine myocardium metabolic pathways [ 29 ] and in murine placental response [ 24 ] are described. The increase of gene expression of proteases involved in ECM-remodeling (Table 2 ) is in concordance with our previous results showing that the parasite increased expression and activity of matrix metalloproteases (MMP-2 and MMP-9) in human placenta [ 19 ].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In addition, ECM components, that are synthetized by the resident cells are also present in tissue and organ samples [ 18 , 19 ]. Similar results have been obtained in animal models, where important changes in murine myocardium metabolic pathways [ 29 ] and in murine placental response [ 24 ] are described. The increase of gene expression of proteases involved in ECM-remodeling (Table 2 ) is in concordance with our previous results showing that the parasite increased expression and activity of matrix metalloproteases (MMP-2 and MMP-9) in human placenta [ 19 ].…”
Section: Discussionsupporting
confidence: 82%
“…To understand the nature of the interaction between upregulated or downregulated genes, we performed a gene interaction analysis using the GeneMANIA plug-in for Cytoscape 3.0 software [ 24 , 25 ]. For each experimental condition, we analyzed co-expression, co-localization, physical interactions, genetic interactions shared protein domains and pathways amongst all the differentially expressed genes (Fc ≥ 2) in both upregulated or downregulated gene lists.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting study on the genetic response of the placenta in chronic experimental infections in mice compared the virulence of T. cruzi K98 clone with an isolated parasite from a congenitally infected child (VD/TcVI), and demonstrated that the murine placental infection with the VD isolated parasite was associated with upregulation of genes related to components of the innate immune system and IFN-γ. Even so, no congenital transmission was observed in pups born to infected mice with VD nor K98 parasites (Juiz et al., 2017). The VD/TcVI parasite proved to be more infective in the human trophoblast-derived cell line BeWo compared to the T. cruzi Y strain/TcII (Medina et al., 2018), probably due to a higher virulence and placental tropism, as it was isolated from a human case of congenital infection (Risso et al., 2004).…”
Section: Parasite Diversity and The Placental Barriermentioning
confidence: 99%
“…Therefore, the widespread implementation of control measures for other forms of infection, such as congenital transmission, is necessary, and can be defined as a global problem because of its presence in endemic and non-endemic areas 5 . Little attention has been paid to this transmission and although measures have been taken to reduce the number of cases, the genetic response in the placental environment against the infection is not well understood 6 . The congenital transmission is important, especially because it does not limit cases to endemic areas but can also affect non-endemic areas due to the increase in migration, which has become the main transmission route for the disease 7 .…”
Section: Introductionmentioning
confidence: 99%